The Characteristic of Black Bakau Fruit as Extract of Antioxidant Source - Fitriany Podunge; Sri Purwaningsih; Tati Nurhayati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Rhizophora mucronata is the dominant species plant in Mangrove forests of Kwandang,North Gorontalo. The objectives of this study were to determine the characteristics of fruitand evaluate antioxidant activity including toxicity and bioactive compound of bakauextract . The morphometric value of the fruit has average length 66,75±3,64 cm and weight110,40±10,84 g. The content of ash, protein, and fat were 98±0,03%, 1,75±0,19 %, and1,69±0,36 %, respectively; and the amounts of soluble, insoluble, and total dietary fiberswere 6,75±1,08, 74,42±1,87, and 81,49±2,40 g/100 g, respectively. The boiling process ofbakau fruit until 30 minutes showed the best activity of toxicity and radical scavenging.The potency of bakau fruit as antioxidant related to the bioactive compounds of its such asflavonoid, hidroquinon, triterpenoid, tanin, and saponin.Keywords: Dietary fiber, Mangrove, morphometric, toxicity